Bacillus velezensis B63 and chitosan control root rot, improve growth and alter the rhizosphere microbiome of geranium - Tarek R. ELSAYED; Nadia A.M. EL-SAID; Fatmah A. SAFHI; Nour El Houda A. REYAD (Phytopathologia Mediterranea)
The root rot complex of geranium plants caused by Rhizoctonia solani and Macrophomina phaseolina is a major threat, and control of these pathogens predominantly relies on chemicals. This study explored multifaceted applications of Bacillus velezensis (strain B63) and chitosan, assessing their biocontrol efficacy against root rot, and their subsequent effects on rhizosphere communities. Strain B63 was antagonistic to R. solani and M. phaseolina. Under field conditions, greatest efficacy was obtained with strain B63 (36% and 33% disease reductions in, respectively, two growing seasons), chitosan soaking + foliar spray 0.2% (CSF 0.2%) (33 and 27% reductions), and 0.1% chitosan soaking + foliar spray (CSF 0.1%) (33 and 26% reductions). These treatments also changed rhizosphere microbiota, as shown by numbers of colony-forming units (CFU) and 16S rRNA gene microbiome analyses. Concomitant with rhizosphere shifts, essential oil yields and composition were positively affected, as shown by gas chromatography analyses. Chitosan soaking + foliar spray 0.2% increased concentrations of citronellol (1.36-fold), geraniol (1.37-fold), citronellyl formate (1.54-fold), and geranyl formate (1.94-fold) in geranium essential oil, compared with the experimental controls. Strain B63 also increased these essential oils by 1.04- to 1.27-fold. B63 also enhanced eugenol levels by 1.35-fold. Treatments with B63 were more effective than chitosan in improving the geranium plant morphological parameters (plant height, numbers of branches, biomass). These results show that B. velezensis strain B63 treatments have potential for enhancing yields and product quality from geranium plant under root rot infection.